A case control study to determine the role of vitamin D in the risk of coronary artery disease among type 2 diabetic individuals - Kumar, Manoj; Pandey, Sanjeev Kumar; V., Vijayavarman; K., Kiran; Kumar, Arun (International Journal of Research in Medical Sciences, 2019)
Background: Diabetes Mellitus comprises a group of metabolic disorder leading to hyperglycaemia. Vitamin D deficiency plays a role in Type 2 Diabetes Mellitus pathogenesis. Vitamin D appears to affect several metabolisms that have been associated with coronary artery disease. Vitamin D level has been recently considered as an adjustable risk factor of cardiovascular diseases, in individuals with type 2 Diabetes. Methods: This case control study was conducted in the Department of Medicine, UPUMS. 100 diabetic individuals with low Vitamin D level were taken as cases and 100 diabetic individuals with normal vitamin D level as control. History and examination with necessary investigations were done. Patients with positive history were subjected to investigations to diagnose CAD. Results: The proportion of case and controls had no significant difference in age distribution. The risk of coronary artery disease was 2.76 times higher among diabetes mellitus patients with vitamin D deficiency (1.36-5.59). The risk of CAD was adjusted for various risk factors (age, sex, hypertension, smoking, physical activity, and lipid profile) Odds ratio was found to be 2.8 (95% CI-1.19-6.94, p-0.018). Conclusions: Vitamin D deficiency among diabetes patients was found to be an independent risk factor for CAD after adjusting other risk factors emphasizing that vitamin D can be a potential risk factor for development of coronary artery disease.